Efektivitas Pembelajaran Elektronik (E-Learning) Dalam Pelatihan Dan Pengembangan Kompetensi Pegawai Sebagai Dampak Pandemi Covid-19 Pada KPKNL Metro - Prasetiya, Rudi; Yateno, Yateno (Universitas Muhammadiyah Metro, 2022)
This study aims to determine the effectiveness of electronic learning (e-learning) in training and developing employee competencies as a result of the covid-19 pandemic at KPKNL Metro. This research is a qualitative descriptive type with data collection techniques through interviews, questionnaires, observation and documentation. The subjects of the research were KPKNL Metro employees. The data analysis technique in this study uses descriptive qualitative data analysis interactive model from Miles and Michael Huberman which consists of three concurrent activity paths, namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that 1) In training and employee competency development after the covid-19 pandemic there are additional ways to participate in training, employees do not need to travel to the training location and train using electronic learning methods (e-learning). 2) The advantages of electronic learning (e-learning) are that it is more flexible in terms of time, more flexible in terms of place and more cost-effective. The drawbacks are the internet network is less stable, computer/laptop equipment facilities are still lacking for some employees, there is no special room for employees to take e-learning, and participants feel bored more easily. 3) The implementation of training and employee competency development through electronic learning (e-learning) as a result of the covid-19 pandemic at the KPKNL Metro is running effectively. 4) Some things that need to be improved so that electronic learning (e-learning) can run better, namely improving the quality of the internet network and increasing internet quota, providing computer/laptop equipment facilities with good conditions for all employees and providing a special room for employees to participate e-learning.